Determination of the Crystal Structure of a New Polymorph of Theophylline. Issue 24 (16th April 2013) - Eddleston, Mark D.; Hejczyk, Katarzyna E.; Bithell, Erica G.; Day, Graeme M.; Jones, William
Abstract A new approach to crystal structure determination, combining crystal structure prediction and transmission electron microscopy, was used to identify a potential new crystal phase of the pharmaceutical compound theophylline. The crystal structure was determined despite the new polymorph occurring as a minor component in a mixture with Form II of theophylline, at a concentration below the limits of detection of analytical methods routinely used for pharmaceutical characterisation. Detection and characterisation of crystallites of this new form were achieved with transmission electron microscopy, exploiting the combination of high magnification imaging and electron diffraction measurements. A plausible crystal structure was identified by indexing experimental electron‐diffraction patterns from a single crystallite of the new polymorph against a reference set of putative crystal structures of theophylline generated by global lattice energy minimisation calculations.